Modified method for bronchial suture by Ramirez Gama compared to separate stitches suture: experimental study - Vitor Mayer de Moura (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: To experimentally compare two classic techniques described for manual suture of the bronchial stump. METHODS: We used organs of pigs, with isolated trachea and lungs, preserved by refrigeration. We dissected 30 bronchi, which were divided into three groups of ten bronchi each, of 3mm, 5mm, and 7mm, respectively. In each, we performed the suture with simple, separated, extramucosal stitches in five other bronchi, and the technique proposed by Ramirez and modified by Santos et al in the other five. Once the sutures were finished, the anastomoses were tested using compressed air ventilation, applying an endotracheal pressure of 20mmHg. RESULTS: the Ramirez Gama suture was more effective in the bronchi of 3, 5 and 7 mm, and there was no air leak even after subjecting them to a tracheal pressure of 20mmHg. The simple interrupted sutures were less effective, with extravasation in six of the 15 tested bronchi, especially in the angles of the sutures. These figures were not significant (p = 0.08). CONCLUSION: manual sutures of the bronchial stumps were more effective when the modified Ramirez Gama suture was used in the caliber bronchi arms when tested with increased endotracheal pressure.